A Collaborative Model for Funding Indonesia’s MBG Program Through Government and Philanthropy Partnerships - Koswara, Asep; Herlina, Lina (Journal of Islamic Economics and Philanthropy, 2025)
Indonesia’s Makan Bergizi Gratis (MBG) program faces significant funding constraints, making its long-term sustainability uncertain. Given the limitations of government financing, this study explores a collaborative funding model that integrates public, philanthropic, and private sector contributions. Using a literature review and case study analysis, the research examines funding mechanisms from successful international programs and assesses their applicability to Indonesia. Findings highlight effective public-philanthropy partnerships in countries such as Brazil, India, and the UK. Brazil’s Fome Zero program successfully reduced hunger through strong government commitment and private sector engagement. India’s Akshaya Patra Foundation scaled its school meal initiative by leveraging corporate social responsibility (CSR) funding, while the UK’s Magic Breakfast demonstrated how philanthropy can complement government efforts in ensuring food security for students. These cases illustrate how multi-sectoral collaboration enhances financial stability, operational efficiency, and program reach. This study provides practical recommendations for policymakers and philanthropic organizations to optimize financial contributions and governance structures. By fostering strong multi-sectoral collaboration, this model can serve as a replicable framework for other large-scale social programs.